Pengembangan Packaging (Kemasan) pada UMKM Rumput Laut di Desa Panda Kabupaten Bima - Irma Mardian; Dewi Sekarwangi; Yunita Haryani; Silvi Lili A; Adinda Faudilah A; Adelia Maryam; Putri Setia N (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This seaweed management activity as a regional specialty was carried out during the MBKM KKN-T activity for the Creative Business Planning (PBUK) course in Panda Village. The aim of this service activity is to help create product innovations from local potential to help increase the income of the Panda Village community. Seeing the existing opportunities, we conducted training in making attractive packaging with the aim of helping develop regional potential. Elements that influence product sales such as product quality, service, marketing and packaging also support each other. So, it is not certain that if the product is of good quality there will be many people interested, unless the consumer really needs it.